The level of endogenic intoxication in the dynamics of development of experimental contact dermatitis and experimental pneumonia and their correction by thiotriazoline - Regeda-Furdychko, M. M. (Journal of Education, Health and Sport, 2019)
Тhe aim of our work was to find out the peculiarities of changes of endogenous intoxication indices in guinea pig blood during the formation of combined pathology - experimental contact dermatitis and experimental pneumonia and correction of their disorders with thiotriazoline. The paper found a gradual increase in the molecules of medium mass and erythrocyte index of intoxication in guinea pig serum with experimental contact dermatitis and experimental pneumonia with the highest degree of expression on the 18th day of the experiment, and this may be may indicate the development of endogenous intoxication of the animal body. At the same time, the use of the drug thiotriazoline caused the decrease of the studied indicators, which gives grounds to state its positive effect on certain markers of endogenous intoxication and the feasibility of further research.